Influence of Feeding Albizia lebbeck and Terminalia arjuna Leaves on Growth Performance and Nutrient Utilization in Surti Kids - Patel, V.R.; Choubey, M.; Raval, A.P.; Desai, M.C. (Indian Journal of Animal Nutrition, 2018)
Thirty growing Surti kids were divided into five treatments of six animals each to evaluate the effects of feeding Albizia lebbeck (AL) and Terminalia arjuna (TA) leaves on growth performance and nutrient utilization. The kids in treatment T1 (control) were fed with basal diet containing 200 g of green jowar which was replaced with AL leaves (T2), TA leaves (T2) or equal mixture of AL and TA leaves in treatment T4 (200 g) and T5 (300 g). The nutrient intake was not affected by feeding of tree leaves. Digestibility of all the nutrients and fibre fractions were higher (P<0.05) in treatmnetT4 which was at par with treatments T3 and T1. Balances of nitrogen and Ca (% of intake) were similar in all the groups while that of phosphorus was higher (P<0.05) in treatment T4. Growth rate was higher in treatment T3 (45.04Â±0.56 g) and lower in T2 (37.25Â±0.57 g). FCR was similar in all the treatments. Cost of feeding showed a reduction due to inclusion of tree leaves while economics of growth (Feed cost/kg gain) was comparable among groups. It could be concluded that replacement of sorghum with TA leaves improved the digestibility and growth performance without affecting economics in terms of cost/kg gain.